2002
DOI: 10.1177/0148607102026006382
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the raw material to the aluminum contamination in parenterals

Abstract: Comparing the aluminum in commercial products and substances, it can be concluded that the contamination may occur in parenterals because aluminum is present naturally in the chemicals. However, when the composition and concentration of the parenteral solution are considered, the contamination of calcium gluconate, trace elements, some vitamins, phosphates, bicarbonate, and heparin cannot be related only to the raw substances. The aluminum level present in these commercial formulations is too high to come only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…In the most recent (2001) American investigation, Buchman et al also reported considerably higher values (1À8 lM/L) than in our coconuts and thus higher than the FDA's recommendations [26]. Likewise, Bohrer et al in a study from Brazil in 2002 also reported values between 0.3 lM/L and 300 lM/L, with almost all amino acid solutions being in excess of the FDA recommendation [27]. Our GCW is thus healthier than most commercial solutions.…”
Section: Minor Elements (Lm/l)supporting
confidence: 50%
“…In the most recent (2001) American investigation, Buchman et al also reported considerably higher values (1À8 lM/L) than in our coconuts and thus higher than the FDA's recommendations [26]. Likewise, Bohrer et al in a study from Brazil in 2002 also reported values between 0.3 lM/L and 300 lM/L, with almost all amino acid solutions being in excess of the FDA recommendation [27]. Our GCW is thus healthier than most commercial solutions.…”
Section: Minor Elements (Lm/l)supporting
confidence: 50%
“…Aluminumcontaining casein hydrolysates, used as protein components of TPN, were associated with patchy osteomalacia [42]. Casein is no longer used, but the possibility of aluminum overloading continues to be a concern [43,44]. Excessive vitamin D can also be deleterious to bone metabolism by suppressing PTH secretion and stimulating bone resorption, with a potential benefit when the supplement is discontinued [45,46].…”
Section: Bone Diseasementioning
confidence: 99%
“…This exposure may occur by dietary intake through feed or water [2,3] as well as through drugs, parenteral nutrition [4,5], and hemodialysis solutions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals such as solutions for parenteral nutrition may have Al [4,5,26] and Si [27] contamination, especially if there is an affinity between the components and Al and/or Si [28]. The volume given to a patient in total parenteral nutrition (TPN) may reach 3000 mL per day, depending on the body weight.…”
Section: Introductionmentioning
confidence: 99%